Housing pay schemes as a strategy to address housing shortages: a case of Harare City Council - Chideme, Dominic (Midlands State University, 2018)
The research main aim was to investigate the effectiveness of housing pay schemes in the provision of urban housing in Harare. Housing Pay Schemes are defined as schemes by which a Local Authority allocates an unserviced piece of land to individuals who then combine their resources together in order to service the land. The introductory chapter highlighted on the background of the study citing the history of Harare city council that led to the adoption of housing pay schemes as an approach to housing service delivery in 2016. Housing pay scheme approach has been there in the country after independence used by the government under the name Pay for your own housing and was adopted by many urban local authorities including Harare city council as a means to provide decent housing and accommodation to the ever growing population in urban areas. The main research question of the study was Has City of Harare chose the best strategy or approach to address housing backlog? A review of literature from published texts, internet sources and journals was gathered and analyzed in the context of the research objectives. The research used case study research design in carrying out the research and used a sample size of 100 respondents from Harare city council, pay scheme members and waiting list applicants. Purposive and convenience sampling techniques were used to select council employees’ respondents and residents from pay schemes as well as those pooled from waiting list applications. Questionnaires and interviews were research instruments. The data collected was analyzed, interpreted and presented in the form of tables, graphs and pie chart. The overall response rate from the questionnaire and interviews was 71%. The major findings of the study showed that there are many challenges that are prohibiting housing pay schemes from being effective like lack of a regulative framework of pay schemes, corruption, and political interference. . Recommendations were made by the researcher for both the housing cooperatives and council for them to increase their ability in providing housing which include a shift of housing delivery models from the focus on home ownership to a focus on rental housing, using tax breaks when engaging PPPs and that to be constructed housing must be high rising flats.